The microbiome of otitis media with effusion in Indigenous Australian children. Issue 9 (September 2015) - Jervis-Bardy, Jake; Rogers, Geraint B.; Morris, Peter S.; Smith-Vaughan, Heidi C.; Nosworthy, Elizabeth; Leong, Lex E.X.; Smith, Renee J.; Weyrich, Laura S.; De Haan, Jacques; Carney, A. Simon; Leach, Amanda J.; O'Leary, Stephen; et al.
Abstract Introduction Indigenous Australian children have a high prevalence of otitis media with effusion (OME) and associated conductive hearing loss. Only three microbiological studies of middle ear fluid (MEF) from Indigenous Australian children with OME have been reported. All of these were reliant on culture or species-specific PCR assays. The aim of this study was to characterise the middle ear fluid (MEF), adenoid and nasopharyngeal (NP) microbiomes of Indigenous Australian children, using culture-independent 16S rRNA gene sequencing. Methods MEF, NP swabs and adenoid specimens were collected from 11 children in the Alice Springs region of Central Australia. Bacterial communities in these specimens were characterised using 16S rRNA gene sequencing. Results The microbiota in MEF samples were dominated (>50% relative abundance) by operational taxonomic units (OTUs) consistent with Alloiococcus otitidis (6/11), Haemophilus influenzae (3/11) or Streptococcus sp. (specifically, Mitis group streptococci which includes Streptococcus pneumoniae) (1/11). Anatomical site selectivity was indicated by the presence of a single conserved Haemophilus OTU in 7/11 MEF samples. In comparison, there were ten distinct Haemophilus OTUs observed across the NP and adenoid samples. Despite significant differences between the MEF and NP/adenoid microbiomes, Streptococcus sp., H. influenzae and Moraxella catarrhalis OTUs were common to all sample types. Co-occurrence of classical otopathogens in paired MEF and NP/Adenoid samples is consistent with earlier culture-based studies. Conclusion These data highlight the need to further assess H. influenzae traits important in otitis media and to understand the role of canal flora, especially A. otitidis, in populations with a high prevalence of tympanic membrane perforation.